Posterior mediastinal teratoma with abdominal extension. Issue 10 (October 1990) - el Kalla, S; Abdul-Hameed, M; al Ashbal, A; Menon, N
Abstract : Posterior mediastinal benign teratomas are uncommon neoplasms in infancy; nine cases have been reported so far. A one month old baby was found to have a benign posterior mediastinal teratoma infiltrating the lower oesophagus from the level of the carina through the oesophageal hiatus into the upper abdomen. Partial oesophagectomy provided a successful outcome.